Muṣṭafá Alī's Epic deeds of artists : a critical edition of the earliest Ottoman text about the calligraphers and painters of the Islamic world - Âli, Mustafa bin Ahmet, 1541-1599. (Islamic History and Civilization, 2011)
The earliest known Ottoman literary source about the lives and works of calligraphers, painters, limners, and book-binders of the Ottoman and Persianate worlds, Mustafa ʿÂli's (1541-1600) Epic Deeds of Artists (1587), was hitherto considered to be primarily a biographic dictionary. Based on a comprehensive reading of the descriptive and analytic tools of ʿÂli's biographical writings as well as his passionately penned personal reflections on sixteenth-century attitudes toward art and artists, this critical edition by Esra Akın-Kıvanç brings to the fore the significance of Epic Deeds not only as a guide to the connoisseurs and aficionados of the time, but also as a fascinating commentary by a prominent intellectual on the spiritual meaning and material value of art.